Optimization of Batik Motif Identification Using Canny Edge Detection - Tamam, moh badri; Kusuma, Suteja Wira Dana; Supriatin, Supriatin; Anwari, Anwari (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2025)
Madura Batik has distinct characteristics in each of its regencies, differing in patterns, colors, and motifs. Therefore, this research employs digital image processing to identify the unique motifs of Madura Batik. The Canny edge detection method is implemented to recognize batik motifs by detecting edges in batik images. The color spaces used are RGB, HSV, and Lab, while the threshold values applied in the Canny operation are (500,500), (300,500), and (100,500). Based on several experiments conducted, the Lab color space with a threshold of (500,500) yields the best edge detection quality.